Fluid balance, thermoregulation and sprint and passing skill performance in female soccer players - Ali, A.; Gardiner, R.; Foskett, A.; Gant, N. (Scandinavian Journal of Medicine & Science in Sports, 2011)
Ten females performed 90 min of the Loughborough Intermittent Shuttle Test (LIST) on two occasions separated by 7 days. Water [3 mL/kg body mass (BM)] was provided every 15 min during exercise (FL); no fluid was given in the other trial (NF). Participants performed the Loughborough Soccer Passing Test (LSPT) before and every 15 min during the LIST. Core temperature (Tc) was measured throughout using ingestible temperature sensors. Heart rate (HR), blood lactate ([La-]) and ratings of perceived exertion (RPE) were collected at regular intervals during exercise. Participants experienced greater BM loss in NF (2.2 ± 0.4%) than FL (1.0 ± 0.4%; P<0.001). Sprint performance deteriorated by 2.7% during exercise (P<0.001) but there was no difference between trials (P=0.294). No significant differences in LSPT performance were detected between trials (P=0.31). Tc was higher during exercise in NF and was 38.6 ± 0.3 °C (NF) and 38.3 ± 0.3 °C (FL; P<0.01) after 90 min. HR (P<0.001), [La-] (P<0.01) and RPE (P=0.009) were higher during exercise in NF. Ingesting water during a 90-min match simulation reduces the mild dehydration seen in female soccer players when no fluid is consumed. However, there was no effect of fluid ingestion on soccer passing skill or sprint performance.